Modifikasi Model Pembelajaran Discovery Learning Dengan Strategi Tugas Dan Paksa Sebagai Upaya Meningkatkan Kemampuan Koneksi Matematis Siswa - Aldan Aldiyansyah; Irvan Rahmatulloh; Lintang Alviandini (Student Research Journal, 2024)
Mathematics is a very important subject in school. In mathematics, there are many skills that students must have. Students who study mathematics must process their mathematical connection skills by connecting mathematics with everyday life. However, in reality, students' mathematical connection abilities are still low. Efforts to improve students' mathematical connection abilities are by implementing the discovery learning learning model. From several studies, the discovery learning model can improve student learning outcomes. Unfortunately, this model still has several shortcomings. One solution for developing a discovery learning model is to modify it with task and force strategies. The forced assignment strategy is to provide assignments with a little coercion as motivation for students in the learning process.